Tujuan Hukum Berkeadilan Dalam Relasi Negara, Masyarakat Dan Kelompok Minoritas Di Indonesia - Anggoro, Setyo Bimo; Rochman, M. Zainur; Amrullah, Arief; Setyawan, Fendy (Jurnal Ilmiah Penegakan Hukum, 2024)
This writing aims to capture, examine, and analyze issues related to violations occurring in Indonesia experienced by minority groups. Additionally, it seeks to analyze and delve deeper into the challenges and solutions in realizing legal objectives in Indonesia regarding the protection of minority groups. The prevalence of intolerance throughout human history has often led to violent actions against minority groups, both physically and psychologically. Indeed, violence is not only perpetrated by individuals or groups but is also carried out by the state. The focus of the problem is on the state's conception of providing protection to minority groups and the extent of the government's role in minimizing these violations to achieve the just goals of the law. This study employs the legal research method to address the raised issues. In the discussion, the government should anticipate not contributing to intolerant attitudes, both through policy products and actions. Moreover, the state should take decisive actions against all forms of intolerance experienced by minority groups and be responsible for the recovery of minority groups who have become victims